Evaluation of mechanical properties of Malaysia local source wood for electric cruiser board applications / Mohamad Rosman Othaman - Mohamad Rosman, Othaman (2020)
This research project revolves around the idea to reduce the carbon emission in mitigating the issue of climate change. An idea to introduce the electrical cruiser board by Muhammad Fiqkri Ismail from Universiti Kuala Lumpur with his idea to promote carbon less form of multimodal transportation for users in urban city of Greater Kuala Lumpur leads this research to study the elastic properties of local source woods in Malaysia that could be proposed for this application. The wood is used for the construction of the deck of cruiser board which designed three layers with the cross-ply laminate. Three types of wood were selected for this research project. It is consisting of Bakau, Merawan, and Laran which all of them had gone through an experimental to evaluate their elastic properties in Forest Research Institute Malaysia (FRIM). The elastic properties as in the form of multilayer were predicted by using laminate composite theory. The result of elastic properties predicted proves that Bakau is the best candidate to be proposed for development of electric cruiser board due to higher elastic properties especially in flexural modulus. The three layers of laminate exhibits significantly higher flexural modulus in longitudinal direction. The additional lamina into seven layers improved significantly of flexural modulus in perpendicular direction and slightly diminished modulus in longitudinal direction.